The Dynamic Impact of Trade Openness on Poverty: An Empirical Study of Indonesia’s Economy - Agusalim, Lestari (International Journal of Economics and Financial Issues, 2017)
This research aims to analyze the dynamic impact of international trade openness on poverty in Indonesia. Previous research shows different effects in every country. The data used are export import value, GDP, income per capita, open unemployment rate, and poverty rate during 1978-2015. VECM analysis shows that in short run, trade openness does not have any significant impact on poverty. However, in long run, it has significant impact in reducing poverty. IRF analysis concludes that poverty rate gave a positive response in the first two years, but negative in the third to every trade openness variable shock. Poverty rate shows the biggest negative response in the fifth year. According to FEVD analysis, trade openness does not give big contribution in affecting poverty rate during the first three years, but starts to show effect in the following seven, with the biggest in the ninth year. Keywords: Trade openness, poverty, VECM JEL Classifications: C10, F14, I32